2019
DOI: 10.1371/journal.pone.0220508
|View full text |Cite
|
Sign up to set email alerts
|

Suicide by hanging: Results from a national survey in Switzerland and its implications for suicide prevention

Abstract: Background Hanging is a frequent suicide method, but developing measures to prevent suicide by this method is particularly challenging. The aim of this study is to gain new knowledge that would enable the design of effective of measures that would help prevent suicide by hanging. Methods A total of 6,497 suicides registered across the eight Swiss Forensic Institutes (IRM) were analysed. Of these, 1,282 (19.7%) persons hung themselves. T-test and chi-square tests. and chi-square tests were used to analyse. . .(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The current scoping review has identified that whilst the literature regarding hanging suicides and prevention is expanding, the rates of near-lethal hangings and suicide death by hanging continue to rise in much of the world (Ganesan et al 2018;Reisch et al 2019;World Health Organization 2019). As Biddle et al (2010) suggested more than a decade ago, there exists a need for research to uncover the current perceptions of hanging, as well as the knowledge individuals draw upon and/or are influenced by when planning suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current scoping review has identified that whilst the literature regarding hanging suicides and prevention is expanding, the rates of near-lethal hangings and suicide death by hanging continue to rise in much of the world (Ganesan et al 2018;Reisch et al 2019;World Health Organization 2019). As Biddle et al (2010) suggested more than a decade ago, there exists a need for research to uncover the current perceptions of hanging, as well as the knowledge individuals draw upon and/or are influenced by when planning suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently shown that reducing access has a positive effect in lowering both method-specific and overall rate of suicide (Pollock 2019). Arguably, fewer opportunities exist in the prevention space for reducing suicide by hanging as ligatures are so universally available, as are ligature points including low-hanging suspension sites (Arya et al 2019;Biddle et al 2010;Gunnell et al 2005;Reisch et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many works by foreign scholars study gender, age, social, regional and cultural factors in connection with suicides by hanging. For example, Reisch T., Hartmann C., Hemmer A., Bartsch C. [7] analyzed 6,497 suicides registered at eight Swiss Forensic Institutes (IRMs), of these, 1,282 (19.7 %) committed suicide by hanging. Based on the used statistical tests, it was proved that in cases of suicide by hanging in the groups "men" and "women", no significant differences were found in socio-demographic variables [7].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the group of suicides, the leading cause of death was hanging, which may reflect the nature of the prison environment. 19 Even though means sufficient to achieve the compression of the neck are generally easy to find in prison, we have also recorded unusual methods of suicide, 20 in which the prisoners used alternative means (e.g. plastic bags, knives and inhalation of butane gas from gas cans).…”
Section: Discussionmentioning
confidence: 95%